Developing Flash Card 'Flat Facts' Media to Enhance Creative Thinking Skills in Elementary Geometry Learning - Fadhilah, Febri Mayasari Miftakhul; Kusuma, Dani (Papanda Publisher, 2025)
Creative thinking skills are fundamental competencies that must be developed in elementary mathematics education, particularly in geometry learning. However, Indonesian students' creative thinking abilities remain low, as evidenced by international assessments like TIMSS and PISA. This study aimed to develop Flash Card